Design Construction and Training on Making Electric Wheelchairs for Instructors at SLB-D YPAC Bandung City to Improve the Mobility Orientation Ability of Physically Impaired Students - Sudrajat Sudrajat; Budi Setiadi; Toto Tohir; Endang Habinuddin; Supriyanto Supriyanto (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Paralympic students in grades 1 to 12 with permanent disabilities in the movement organs (bones, joints, muscles) in the Special School category D (SLB-D) YPAC Bandung City have been equipped with basic Mobility Orientation (OM) technical skills to be able to carry out activities and mobility. Independent. One of the OM techniques taught to people with quadriplegia in the categories of Paraplegia (abnormalities in both legs and feet) and Diplegia (abnormalities in both hands or paralyzed legs) is the use of a manual wheelchair. Even though all quadriplegic students already have OM abilities. However, many students are reluctant to use manual wheelchairs independently. The problem is because it is considered to drain stamina, difficulty controlling it, and fear of using it on uphill/downhill/sloping/potholed roads. So it was proposed that the mobile electric wheelchair be controlled by the physically disabled via a manual button, and as a safety measure, it is equipped with an anti-crash sensor. Anti-crash sensors help the wheelchair move automatically (slow down, stop) if an object is in the way. In implementing this PKM, the team carried out knowledge and technology transfer to Instructors/Teachers/Parents of Students and testing for the Physically Impaired. The results of this activity are in the form of electric wheelchairs that have been tested.